Mapping the Landscape of Sustainopreneurship Research: A Global Bibliometric Analysis (2000–2025) - Judijanto, Loso; Setiyawan, Heri (West Science Interdisciplinary Studies, 2025)
This study presents a comprehensive bibliometric analysis of sustainopreneurship research spanning the period 2000–2025, aiming to map its intellectual structure, thematic evolution, and global research collaboration patterns. Using data extracted from the Scopus and Web of Science databases, a total of 320 documents were analyzed through performance analysis and science mapping techniques using VOSviewer and Biblioshiny. The findings reveal that sustainopreneurship—defined as entrepreneurship and innovation for sustainability—has evolved from a conceptual niche into a dynamic, interdisciplinary research field bridging sustainable development, social innovation, and digital transformation. The keyword co-occurrence and overlay visualizations highlight five dominant research clusters: (1) sustainable development and circular economy, (2) sustainability-oriented entrepreneurship, (3) education and entrepreneurial intention, (4) regional development and empowerment, and (5) bibliometric and digital entrepreneurship studies. Collaboration network analyses identify India, the United States, China, Germany, and Spain as leading contributors, with emerging participation from developing regions such as Indonesia, Brazil, and South Africa. The results underscore the growing internationalization and diversification of sustainopreneurship research, driven by the integration of sustainability, innovation, and technology in business and education. This study contributes to the literature by providing a systematic and visualized overview of the global knowledge landscape, clarifying conceptual overlaps, and outlining future research directions for theory development, policy alignment, and practical implementation of sustainopreneurship in achieving the Sustainable Development Goals (SDGs).